1998
DOI: 10.1111/j.1600-079x.1998.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to 2.9 mT, 40 Hz magnetic field reduces melatonin concentrations in humans

Abstract: Diurnal rhythm of serum melatonin concentrations was estimated in 12 men with low back pain syndrome before and after exposure to a very low-frequency magnetic field (2.9 mT, 40 Hz, square wave, bipolar). Patients were exposed to the magnetic field for 3 weeks (20 min per day, 5 days per week) either in the morning (at 10:00 hr) or in the late afternoon (at 18:00 hr). Significant depression in nocturnal melatonin rise was observed regardless of the time of exposure. This phenomenon was characteristic for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
1
25
1
1
Order By: Relevance
“…Support for this hypothesis was found in pinealectomy and constant-light studies, which indicate that eliminating the endogenous nOCturnalmelatonin signal enhances mammary tumorigenesis in female rats (5). Some studies have suggested inhibition of melatonin production in humans mediated by~F exposure (6)(7)(8)(9)(10)(11), while others have not (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Support for this hypothesis was found in pinealectomy and constant-light studies, which indicate that eliminating the endogenous nOCturnalmelatonin signal enhances mammary tumorigenesis in female rats (5). Some studies have suggested inhibition of melatonin production in humans mediated by~F exposure (6)(7)(8)(9)(10)(11), while others have not (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Karasek et al [1998] showed that 40 Hz daytime MF exposure induced a significant depression in nocturnal melatonin rise of patients with low back pain syndrome, regardless of time of exposure (10:00 or 18:00 hr). It is the first study to show that daytime MF exposure can influence night-time production of melatonin in controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be interesting to consider this known interindividual difference observed in healthy subjects [Bergiannaki et al, 1995], according to the divergent results related to this issue [Graham et al, 1996;Karasek et al, 1998;Wood et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…Although EMFinduced suppression on nocturnal melatonin secretion has been reported in occupational and residential studies [15,16,17,18,19,20], in the majority of laboratory-based exposure studies [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39], EMF did not exert a distinct influence on melatonin or 6-hydroxymelatonin concentrations[see 40] (Table 1). According to Karasek et al [28,40], discrepancies in the results may depend on different experimental paradigms, including differences in certain characteristics of the applied magnetic fields, such as field induction, frequency, duration of exposure, timing of exposure, applied vector, etc.…”
Section: Electromagnetic Fields and Melatoninmentioning
confidence: 99%